PGA Estimation of 346 Points in West Sumatra based on Earthquakes Scenario in West Pasaman with Si and Midorikawa Formula - Ramadhan, Wahyu; Syafriani, Syafriani; Fauzi, Ahmad; Dwiridal, Letmi (Journal of Physics and Its Applications, 2024)
There was a destructive earthquake on February 25, 2022, at 08:39:29 WIB with a magnitude of 6,1 Mw that struck western Sumatra with an epicenter on land, and was located on a blind fault. The impact of the earthquake was felt quite widely in all Regencies/Cities in West Sumatra with an intensity of IV – VIII MMI. The earthquake caused damage, an estimated 6627 houses, 70 mosques, 41 offices, 208 schools, 25 medical infrastructure and 5 bridges. Therefore, it is necessary to conduct research in the province of West Sumatra on PGA using the Si and Midorikawa method and intensity with Murphy O'Brein's empirical formulation as an effort to mitigate earthquake disasters. This study aims to determine PGA as the level of earthquake activity and intensity as a measure of the damage caused by earthquakes and to analyze their distribution maps. The data used is earthquake data for the period 1936-2022 with a magnitude ≥ 5 Mw and a depth of ≤ 70 km sourced from the catalog of the National Earthquakes Information Center U.S Geological Survey (NEIC/USGS). The results of data processing produce PGA values in West Sumatra ranging from 0.4083 – 782.9839 gal with an intensity (MMI) ranging from I – IX MMI. Map of distribution of PGA values and the highest intensity is in West Pasaman Regency and the lowest value is in Mentawai Islands Regency. The West Pasaman Regency area and its surroundings should meet the requirements for earthquake-resistant buildings, because they have a fairly high PGA value.